О бифуркациях в случае двукратного вырождения линеаризованной задачи - Дымарский, Я.М. (Нелинейные граничные задачи, 2002)
We study typical bifurcations of the zero solution of continuous operator equation in the case of two-fold degeneracy of linearized problem.